2000
DOI: 10.1007/pl00008207
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of apoptosis and associated factors in oral squamous cell carcinoma

Abstract: Tumour progression is characterised by an imbalance between cell proliferation and apoptosis. The aim of our study was to estimate the importance of proliferation and apoptosis associated parameters in primary squamous cell carcinomas (SCCs) of the oral cavity and oropharynx. For determination of apoptosis, the enzymatic labelling of DNA fragmentation with a terminal transferase reaction was used in 156 tissue samples of 107 patients, including corresponding lymph-node metastases in nine cases. P53, bcl-2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
26
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 44 publications
7
26
0
6
Order By: Relevance
“…The amount of apoptosis seen in carcinomas varied ( Figure 1B), with a range of apoptotic indices from 0.03 to 2.25%. The amount of apoptosis that we observed in the TUNEL assay was generally similar to that reported by others (Xie et al, 1999;Macluskey et al, 2000;Stoll et al, 2000). The late stages of apoptosis that result in the distinctive morphology of an apoptotic cell are thought to occur rapidly, followed by phagocytic removal of the apoptotic bodies by neighbouring cells.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The amount of apoptosis seen in carcinomas varied ( Figure 1B), with a range of apoptotic indices from 0.03 to 2.25%. The amount of apoptosis that we observed in the TUNEL assay was generally similar to that reported by others (Xie et al, 1999;Macluskey et al, 2000;Stoll et al, 2000). The late stages of apoptosis that result in the distinctive morphology of an apoptotic cell are thought to occur rapidly, followed by phagocytic removal of the apoptotic bodies by neighbouring cells.…”
Section: Resultssupporting
confidence: 89%
“…Tumour cells can acquire resistance to apoptosis by various mechanisms that interfere at different levels of apoptosis signalling and involve both the death receptor and mitochondrial pathways (Igney and Krammer, 2002). Previous studies of apoptosis in OSCC have described a correlation between high AI and well-differentiated carcinomas (Xie et al, 1999) and between the antiapoptotic protein Bcl-2 and high histological grade (less differentiated carcinomas) (Jordan et al, 1996;Stoll et al, 2000). Our data indicate the opposite relationship of low AI in well-differentiated tumours, and provide an explanation for tumour cell accumulation in welldifferentiated carcinomas that have a low proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researches have focused on the significance of Ki-67 in squamous cell carcinoma of head and neck (Girod et al, 1998;Sittel et al, 1999;Stoll et al, 2000;Bettendorf and Herrmann, 2002;Carinci et al, 2002;Myoung et al, 2006). This heterogeneous result showed the correlation of Ki-67 expression to tumor phenotype factors.…”
Section: Discussionmentioning
confidence: 95%
“…There are several reports showing no association between p53 overexpression and prognosis in laryngeal carcinoma [26][27][28] and in oral cancer. 57 In contrast to overexpression of p53, the mutation of p53 is likelier to be associated with an unfavorable clinical course in head and neck SCC. In advanced laryngeal carcinoma, Bradford et al 58 reported that p53 mutation is associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%